2014
DOI: 10.17129/botsci.102
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of the phlorotannins dieckol and phlorofucofuroeckol-A from Ecklonia cava against Propionibacterium acnes

Abstract: Methanol extract of the marine brown alga Ecklonia cava has been shown to exhibit antimicrobial activity against Propionibacterium acnes. To identify the compounds conferring this antimicrobial activity, methanol extract was fractionated using silica-gel column chromatography by increasing solvent polarity, and the antimicrobial activities of each fraction were determined in terms of the minimum inhibitory concentration. Hexane, diethyl ether, acetone, ethyl acetate, acetonitrile, methanol, and water fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“… a Confirmed with Mass Spectroscopy (MS) fragmentation and European MassBank results; b Confirmed with Mass Spectroscopy (MS) fragmentation and Phenol-Explores 3.6 results; c Confirmed based on Choi et al [ 22 ]. …”
Section: Figurementioning
confidence: 71%
“… a Confirmed with Mass Spectroscopy (MS) fragmentation and European MassBank results; b Confirmed with Mass Spectroscopy (MS) fragmentation and Phenol-Explores 3.6 results; c Confirmed based on Choi et al [ 22 ]. …”
Section: Figurementioning
confidence: 71%
“…At last, size exclusion chromatography (SEC-CC) using Sephadex LH-20 has been repeatedly used in the fractionation of macroalgae polar extracts [60,76,77,88,115,151,156,157,174,175,[177][178][179][180][181][182]. The separation of compounds in Sephadex LH-20 is promoted by the metabolites' molecular size, but also by its solubility in the eluent.…”
Section: Column Chromatographymentioning
confidence: 99%
“…Reversed-phase (RP) HPLC columns have been the most used in macroalgae phenolic rich extracts [32,39,62,73,157,159,169,173,180,182,[186][187][188][189]. Octadecyl ("C18" or "ODS") has been the most used stationary phase, with a particle size of 5 µm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, phlorotannins-β-lactam antibiotics combinations exert a synergistic effect against MRSA, indicating the promising treatment of MRSA infections. In addition, it has shown that phlorofucofuroeckol-A from E. cava and E. bicyclis exhibited effective inhibition against Propionibacterium acnes, which may be useful as natural additives in anti-acne cosmetic products 86,87 . Although the relationship between the structure and anti-bacterial activity of the phlorotannins is limited, their inhibitory activity may be suggested to depend on the degree of polymerization of phlorotannin derivatives.…”
Section: Antimicrobial Activitymentioning
confidence: 99%